The Hybridity of Confectionery in the Jajanan Manuscript NB 499: A Linguistic and Cultural Review - Arsanti Wulandari; Nanda Nursa Alya; Zakariya Pamuji Aminullah (Leksema: Jurnal Bahasa dan Sastra, 2026)
Manuscripts serve as historical documents containing a wealth of information, from historical chronicles to culinary notes that reflect the community's habits and attitudes. This study focuses on the Jajanan (snacks) manuscript (code NB 499) at the National Library of Indonesia, dated circa 1931. The objective of this research is to analyze how linguistic and cultural hybridization is manifested within the snack names and recipes recorded in the text. The study employs a descriptive-qualitative approach within an ethnolinguistic theoretical framework. Data were analyzed using the close reading method, integrated with the distributional method to examine linguistic elements and the referential method to interpret non-linguistic aspects such as vernacularization and hybridization. The results indicate that the snack names are predominantly attributive phrases reflecting a blend of Javanese and foreign cultures (Dutch, French, and English). The findings reveal a process of vernacularization through phonetic adjustments to fit the Javanese phonological system. This phenomenon demonstrates the Javanese community's ability to harmonize and adapt colonial influences into their local cultural identity through adaptive linguistic production.